Modifikasi Metode Full Wave di Sekitar Titik Singular - Titiek Setiawati (Institut Teknologi Bandung, 2002)
Modification of the full wave method is carried out for solving the electromagnetic wave equation in the vicinity of a singular point which is caused by a resonance effect. It is assumed that an inhomogeneous plasma medium is stratified horizontally. Modification towards the transition matrix in the vicinity of the singular point, by using an exponential function and Picard integration is needed for obtaining a unique (convergent) solution. The solution in the form of the electromagnetic field at the top layer can be represented as a multiplication of a number of the transition matrices with the electromagnetic field at the bottom layer.